2010
DOI: 10.1002/gps.2434
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental disorders and service utilization in seniors: results from the Canadian community health survey cycle 1.2.

Abstract: The presence of common mental disorders is lower in seniors as compared to younger adults. Age and gender influence mental health service utilization rates. Copyright © 2010 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
13
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
7
13
2
Order By: Relevance
“…Moreover, age was inversely associated with the likelihood of having had a consultation with a healthcare provider for mental health problems, independently of mental health status. This is consistent with results previously published using similar observational data (Mosier et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, age was inversely associated with the likelihood of having had a consultation with a healthcare provider for mental health problems, independently of mental health status. This is consistent with results previously published using similar observational data (Mosier et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…It has been previously suggested that the likelihood of receiving minimal adequate treatment decreases with age (Garrido, Kane, Kaas, & Kane, 2011;Mosier et al, 2010;Wang et al, 2005). De Beurs and colleagues (1999), for example, reported that less than three per cent of those older adults diagnosed with an anxiety disorder consulted a psychiatrist for their mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…In females, mental health service use was greater in the age groups between 25 and 64 years as opposed to the 65 years and over age group, which has been similarly reported elsewhere [18,33]. Considering that most seniors consult a family physician annually, but that only a few seek treatment for their mental health problems and are treated, [15], better detection of mental health needs especially among older women is needed in primary care.…”
Section: Discussionsupporting
confidence: 52%
“…Although psychiatric disorders are highly prevalent throughout the life course (2,3) and treatable (4,5), little is known about why different stages of the life course differentially impact use of mental health services (69). Prior research has found that adults in younger and older age with psychiatric issues have the lowest services use (6,10).…”
Section: Objectivementioning
confidence: 99%